2001
DOI: 10.1038/sj.onc.1204720
|View full text |Cite
|
Sign up to set email alerts
|

FLRG, an activin-binding protein, is a new target of TGFβ transcription activation through Smad proteins

Abstract: The FLRG gene encodes a secreted glycoprotein that binds to activin and is highly homologous to follistatin, an activin ligand. We cloned the promoter region of the human FLRG gene, and de®ned the minimal region necessary for transcription activation in a reportersystem assay. We showed that the fragment between positions 7130 and +6, which consists of multiple consensus Sp1-binding sites, is required for the constitutive expression of the FLRG gene. We demonstrate here that FLRG mRNA expression is rapidly ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 46 publications
1
24
1
1
Order By: Relevance
“…Interestingly and in contrast to the results of the current study, it has been reported that regulatory elements located between Ϫ2165 and ϩ2 are sufficient for Smad-dependent transcription of the human follistatin gene in HepG2 cells (40,41). These apparently conflicting results could arise from differences in the human and rat follistatin genes or differences in the mechanisms of activation in the two cell types.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Interestingly and in contrast to the results of the current study, it has been reported that regulatory elements located between Ϫ2165 and ϩ2 are sufficient for Smad-dependent transcription of the human follistatin gene in HepG2 cells (40,41). These apparently conflicting results could arise from differences in the human and rat follistatin genes or differences in the mechanisms of activation in the two cell types.…”
Section: Discussioncontrasting
confidence: 56%
“…On the other hand, a luciferase reporter construct designated rFS(rin3)-luc that incorporates ϳ2.8 kb of the 5Ј-flanking sequence and extends into the third intron of the rat follistatin gene is induced by activin in ␣T3-1 cells (39). Finally, it has been reported that the human follistatin promoter is activated in HepG2 cells by Smad signaling, downstream of activin or TGF-␤ (40,41). The present study was undertaken to further evaluate the mechanism involved in the transcriptional activation of the follistatin gene by activin and to identify activin-responsive regulatory elements.…”
mentioning
confidence: 99%
“…Because propeptide is irreversibly removed during the activation process, it is no longer possible to turn off active TGF-␤ using this protein. Interestingly, transcription of FLRG has been shown to be up-regulated upon signaling by both TGF-␤ and activin (29,30). This occurs through binding of activated Smad proteins to a Smad-binding element in the FLRG promoter and results in the increased production of secreted FLRG and the eventual inhibition of activin signaling (29).…”
Section: Fig 6 Flrg Inhibits Myostatin Activity In a Concentrationdmentioning
confidence: 99%
“…Like follistatin, FLRG binds and inhibits activin and multiple BMPs in vitro (26 -28). Transcription of FLRG is up-regulated by activin and TGF-␤ signaling through SMAD proteins, initiating a negative feedback loop that controls TGF-␤ signaling (29,30). To date, however, FLRG has not been tied to a particular growth factor in vivo.…”
mentioning
confidence: 99%
“…Transcription of FSTL3 mRNA was shown to be stimulated by TGF beta and activin A via Smad proteins (Bartholin et al, 2001;Bartholin et al, 2002), which seems to be part of a negative feedback loop as FSTL3 can antagonize activin A (see below). In a different study it was found that GDF9 -another TGF beta superfamily cytokine -can suppress both basal and activin A-induced FSTL3 (and follistatin) mRNA and protein levels in cultured human granulosa-lutein (hGL) cells from women undergoing in vitro fertilization (IVF) treatment (Shi et al, 2011).…”
Section: Transcriptionmentioning
confidence: 99%